Impact of Dialect on the Acquisition of Sounds and their Clusters: the Results of a Non-word Repetition Test - Krivickaitė-Leišienė, Eglė (Taikomoji kalbotyra, 2020)
The paper aims to analyse and compare children’s acquisition of phonotactic patterns in two regional areas in Lithuania: Southern Samogitia and Western High Lithuania. The sample of the study consisted of 48 children: 24 children living in Kelmė (representing the Raseiniškiai subdialect of Southern Samogitian) and 24 children living in Kaunas area (representing the Kauniškiai subdialect of Western High Lithuanian). The data was collected using a non-word repetition test task in Lithuanian. In general, since in Lithuanian dialects vowels differ more than consonants, the pronunciation of vowels serves as one of the main criteria used to define dialects. The main dialect divisions are based on the variants of the stressed diphthongs uo and ie when they occur in the non-final position in a word. In the Samogitian subdialects, the vowels o and ė are pronounced as uo and ie (for example, kuoje [= koja] and dieti [= dėti]); the diphthongs uo and ie are pronounced as long vowels ū and ī. The results of the current research have disclosed that some features of the Raseiniškiai subdialect of Southern Samogitian prevail in children’s language. For example, instead of the vowel o, children employ uo: geluoša [= geloša], talabuosa [= staligosa]; instead of the vowel u, they opt for uo: lasmuove [= lasmuvi]; and instead of the vowel e, they tend to use ei: šveila [= švela]. The results of the research also demonstrate that Lithuanian children apply the typical universal strategies of pronunciation simplification, mostly substitution and omission; other strategies, such as consonant assimilation, metathesis, sound migration to another syllable, and sound addition, were much less frequent.